Abordaje de Terapia Ocupacional a través de la integración sensorial en personas con parálisis cerebral - Vinueza Mera, Gabriela Stefania (2021)
The purpose of this research originates from the sensory integration problems found in children with cerebral palsy which prevents them from carrying out their tasks. It is important to know how to recognize the symptoms of dysfunction that may occur. Additionally, it should be emphasized that the earlier they are found, the better results the rehabilitation process will have in the recognition and intervention of Occupational Therapy, which is essential to detect the exact dysfunction that the child presents, thus, the therapist will help them have a better sensory processing and eventually the infant will be able to carry out their activities more easily, improving their quality of life. Therefore, a bibliographic search was made among 23 scientific articles that allowed to compile information about cerebral palsy, sensory integration and how to recognize and treat a dysfunction, considering the great importance it has because not only does it affect activities of daily and instrumental life, but also it has effects on the social, educational and behavioral sphere.